Strategi Peningkatan Produk Emping Jagung - Mahmud, Fadhilah; Nainiti, Selfius P.N.; Lango, Alfetri N.P. (Undana Press, 2023)
Sinar 313 UKM is one of the industries engaged in the processing of corn chips. This industry needs to carry out a mature strategy and development for the survival of the agro-industry in the future. This is done bearing in mind that in the future the competition will be very tight. The development of MSME agro-industry is largely determined by factors including internal and external. This research uses descriptive analysis method with the process of collecting data through observation and interviews. Meanwhile, to find out the strategy used in SMEs in this study is a SWOT analysis with IFAS and EFAS calculations to determine the strategy to be taken. Furthermore, the data is processed by comparing the level of agreement relative to each other, so that the value of the factors that influence the processed corn is known. The results of this study indicate that there are 10 strategic items that support the productivity of corn chips in Sinar 313 UKM. Some of them are capacity optimization, enlarged market share, intensification of online sales through social media, efficiency, improving production technology, etc. While the obstacles found in this study include the lack of supply of raw materials, weather, inadequate promotion, lack of skilled workforce, and low government attention.